Scruples before Religion: Muslim Waraʿ of the Formative Period - Laaroussi, Omar (AUC Knowledge Fountain, 2026)
This thesis studies the conceptual history of waraʿ and its role as a normative paradigm existing in the formative centuries of the Islamic world. To do so, I consider the Hellenic concepts that ground Near Eastern understandings of virtue and piety before the rise of Islam. This, I then use to contextualise a focused discussion on the textual history of waraʿ before moving on to discuss its properties in a ascetic social-world through the analysis of those very texts. I attempt to place those properties in conversation with modern philosophers’ work on disciplinary regimes and their impacts upon the self.  In Chapter One, I discuss approaches to virtue and piety in the Greco-Roman world, as well as their effects on Abrahamic concepts, by considering the distinction between religio and superstitio in piety followed by the difference between the vita activa and vita contempletiva in virtue. I compare this to Quranic discourse and ḥadīth before moving to a discussion of the networks that were associated with writings on zuhd and waraʿ. I use that to describe both the features that are shared among the books of waraʿ, as well as the author-specific identities that inform the differences among the texts (Chapter 2). I follow that with an analysis of the texts as artifacts of normative thinking in a decentralised social-world and their relationship to a Foucauldian view of discipline (Chapter 3). I conclude by reflecting on the short-lived emphasis of waraʿ and its sublation by larger trends of fiqh and Sufism.